PERAMALAN ANGKA INFEKSI SIFILIS MELALUI TRANSFUSI DARAH DI KOTA PONTIANAK DENGAN FUZZY INFERENCE SYSTEM - Nur Azizah; Ressy Rustanuarsi (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2017)
This study aims to forecast the number of syphilis infections through blood transfusion in Pontianak by using the Fuzzy Inference System with Mamdani method. Data on the number of syphilis infections are divided into two, namely training data (TRD) and checking data (CHD). Data on the rates of syphilis infection in month t-2 and month t-1 are used as inputs, while data in t month are used as output. 20 rules are formed in this system. The Mamdani method is used for inference and the centroid method is used for defuzification. The results of this study indicate that the Fuzzy Inference System with Mamdani method can be used to forecast the rate of syphilis infection with an error rate of TRD of 14.4% and CHD of 34.8%.